Other Minds - Hyslop, Alec.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1995)
This book has been a long time in the making. Other issues have taken me away from it from time to extended time. But I kept coming back to the problem of other minds. It has remained a great issue, it is much contested still, and it is, after all, elose to us all. I like believing that the time taken has deepened my understanding of the problem and how it is to be handled. Other people, some by disagreeing vehemently, have helped greatly. I mention in particular, Brian Ellis, Robert Fox, Graeme Marshali, Tim Oakley, Ray Pinkerton and Robert Young. Robert Pargetter argued with me, and kept insisting that I write this book. John Bigelow, Michael Bradley, Keith Campbell, Frank Jackson, and William Lycan assisted by reading an earlier version and providing valued comments. Frank Jackson has been specially helpful, not just on this topic. He can be blamed for initially causing me to take the analogical inference seriously. Tbe La Trobe Philosophy Department has been a good place to do philosophy. I am grateful to Suzanne Hayster, Sandra Paul, and Betty Pritchard for struggling at various times with various recalcitrant manuscripts. Most particularly I thank Gai Larkin. She has seen the project through, with considerably more than efficiency.
1. What is the problem -- 2. Who has the problem of other minds? -- 3. Other minds and scientific inference -- 4. The analogical inference to other minds -- 5. Criteria and other minds -- 6. The (3z(Bold(3y (Bprivate language argument and other minds -- 7. The (3z(Bnew(3y (Bprivate language argument: Kripstein$1 (Bs new form of scepticism -- 8. (3z(BWittgenstein$1 (Bs(3y z(Battitudinal approach(3y (Bto other minds -- 9. Strawson on other minds -- Notes -- References.s
Keywords: Philosophy of mind; Philosophy and science; Epistemology; Philosophy of Mind; Philosophy of Science; Epistemology